Acid‐suppressive drugs and risk of kidney disease: A systematic review and meta‐analysis. Issue 9 (10th May 2018) - Qiu, Tingting; Zhou, Junwen; Zhang, Chao
Abstract: Background and Aim: More concerns had been raised about the risk of kidney disease (KD) associated with acid‐suppressive drugs. But whether they could directly increase such risk remained unclear. Meta‐analysis was conducted to comprehensively investigate this relationship. Methods: PubMed, EMBASE, Cochrane Central Register of Controlled Trials, and three Chinese databases were searched until April 2017 for observational studies investigating the associations between acid‐suppressive drugs and KD. Pooled log (odds ratios [ORs]) or log (hazard ratios [HRs]) with standard errors for KD risk were calculated using the generic inverse variance method and random‐effect model. Results: Ten studies involving 128 020 KD patients were included. Proton pump inhibitor (PPI) therapy was associated with higher risks of acute interstitial nephritis (OR, 2.78; 95% confidence interval [CI], 1.25–6.17), acute kidney injury (AKI) (HR, 1.85; 95% CI, 1.33–2.59), chronic kidney disease (CKD) (HR, 1.47; 95% CI, 1.03–2.09), and end‐stage renal disease (ESRD) (HR, 1.61; 95% CI, 1.26–2.04) than non‐PPI therapy. Additionally, PPI significantly increased the risks of AKI (HR, 1.32; 95% CI, 1.16–1.51), CKD (HR, 1.28; 95% CI, 1.24–1.33), and ESRD (HR, 1.96; 95% CI, 1.21–3.17) compared with histamine 2 receptor antagonist (H2 RA). Relationship between H2 RA therapy and AKI (OR, 0.98; 95% CI, 0.90–1.07) or CKD (OR, 1.00; 95% CI, 0.89–1.11) was not found. Conclusions: Proton pump inhibitor therapy significantly increased the risks of acute interstitial nephritis, AKI, CKD, and ESRD. Similar risks were not identified for H2 RA therapy. More clinical trials are needed to confirm our findings.